DIMENSI KUALITAS LAYANAN DAN PENGARUHNYA TERHADAP LOYALITAS MAHASISWA DENGAN TINGKAT KEPUASAN SEBAGAI VARIABEL INTERVENING - Gumar Herudiansyah; Mister Candera (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This study aims to analyze and describe the direct influence and indirect influence ofservice quality dimensions on student loyalty through student satisfaction. This study uses perimer data collected through questionnaires with a total of 350 students. Analysis of the data used is Path Analysis. Based on the results of the analysis it was found that tangible has a direct and indirect effect on student loyalty through student satisfaction. reliable variables, responsiveness, and empathy have a direct but not significant effect on loyalty. These three variables have a significant effect on student satisfaction. Meanwhile, assurances have an effect and are not significant towards student loyalty either directly or indirectly through student satisfaction. The results of this study can be used as information for Higher Education in making and implementing policies, so that stude.